MODEL OF INFORMATION SYSTEM OPERATION BASED ON TECHNOLOGY ACCEPTANCE MODEL FOR MICRO FINANCIAL INSTITUTIONS - Atika Jauharia Hatta (Universitas Hayam Wuruk Perbanas, 2011)
Credit union (CU) is an important financial institution for poor society and micro industriesin supporting the fact in which in credit unions, client doesn't require complicated clauseslike other micro finance companies. Yet, traditional ways in accounting system make limitationfor this institution efficient and effective in their operation. By applying an informationsystem, they can increase performance through repairing in planning and managing businessand easier in transaction activity. Thus, it will reduce operation costs. The main objective ofthe research is to develop an electronic transaction system (ETS) for credit unions (CUs) byidentifying determinants that are considered by managers and employees of credit unions inadopting the system. To investigate the determinants for adopting information system, theresearch uses Technology Acceptance Model (TAM) modified by other models such as TRA,TPB and DOI. Using Structural Equation, the result shows supporting evidence for TAM thatperceived ease of use and perceived usefulness are important determinants for adopting informationsystems.